Jane's patisserie : deliciously customizable cakes, bakes & treats - Dunn, Jane (Baker) (Sourcebooks, 2024)
Life is what you bake it - so bake it sweet! Discover how to make life sweet with 100 delicious bakes, cakes and treats from baking blogger, Jane. Jane's recipes are loved for being easy, customisable, and packed with your favourite flavours. Covering everything from gooey cookies and celebration cakes with a dreamy drip finish, to fluffy cupcakes and creamy no-bake cheesecakes, Jane's Patisserie is easy baking for everyone. Whether you're looking for a salted caramel fix, or a spicy biscoff bake, this book has everything you need to create iconic bakes and become a star baker. Includes new and exclusive recipes requested by her followers and the most popular classics from her blog - NYC Cookies, No-Bake Biscoff Cheesecake, Salted Caramel Drip Cake and more!